Learning Unix for OS X - Taylor, Dave, 1962- (O'Reilly, 2016)
"Think your Mac is powerful now? This practical guide shows you how to get much more from your system by tapping into Unix, the robust operating system concealed beneath OS Xs beautiful user interface. OS X puts more than a thousand Unix commands at your fingertips--for finding and managing files, remotely accessing your Mac from other computers, and using freely downloadable open source applications. If youre an experienced Mac user, this updated edition teaches you all the basic commands you need to get started with Unix. Youll soon learn how to gain real control over your system"--Page 4 of cover.